Sociological Analysis of "Abandon the Old in Tokyo" Comic Story by Yoshihiro Tatsumi - Juwita Carolyn Damanik (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. This study aims to compare the social life of Tokyo workers and what Yoshihiro Tatsumi describes in the comic gekiga “Abandon the Old in Tokyo” in the period of Japan’s rapid economic growth (mid 1950-early 1970) using the sociological approach of literary works. Social life that will be studied is specifically on the social interactions of Tokyo workers with society, employers, colleagues, parents and also the form of the worker's family system at that time. The method used in this study is the qualitative descriptive method. The findings showed that the comic story, despite being a work of fiction, does indeed depict the real social conditions of Tokyo workers during a period of rapid economic growth where workers tend to be individualistic and hedonistic. The rapid changes in Tokyo at that time does not carry over into the work environment where workers still adhere to patrilineal management which is very formal, however between colleagues some form of informality and intimacy still exists in the face of extremely difficult working conditions. Meanwhile, the neglect of parents by the younger generation occurs a lot due to changes in the family system changing from the IE system to the kazoku system, the economic and the housing situation, as well as the relationship between family members is no longer close. Marriage no longer occurs to maintain the IE system and customs, rather, marriage occurs on the basis of love between husband and wifeKeywords: Sociological Analysis, Abandon the Old in Tokyo, Gekiga, Workers